THE CONCEPT OF FIVE BREASTFEEDING IN DETERMINING MAHRAM RELATIONSHIPS AND ITS RELEVANCE IN THE MODERN ERA - Widia Astuti; Ruslan Sangaji; Rika Afrinia Wulandari Syam; Hafilah Ramadani; Erzy Aurelia Maharani (LPPM STAI Muhammadiyah Probolinggo, 2026)
The formation of a mahram relationship through breastfeeding is a fundamental aspect of Islamic family law, carrying significant legal consequences, especially in relation to marital restrictions. This study aims to explore the notion of five instances of breastfeeding as a condition for establishing a mahram bond from a fiqh-based perspective and to assess its applicability in contemporary society. A combination of normative and sociological legal approaches is employed, utilizing a literature-based method that examines classical fiqh sources, Indonesian legal frameworks, and scholarly publications. The findings indicate that although the concept of five breastfeeding instances is broadly accepted among Islamic Mazhab, its practical application in modern settings remains complex, particularly regarding documentation and legal verification. Thus, a comprehensive legal framework that harmonizes Shariah principles with national legal systems is essential to ensure the legal clarity of breastfeeding-based mahram relationships, while also safeguarding lineage, marital regulations, and core family values.